Evaluation of blood loss during internal (limb-salvage) hemipelvectomy for pelvic tumours : what have we learned so far? - Sharifudin, Mohd Ariff; Wan Ismail, Wan Faisham Numan; Wan, Zulmi; Mat Zin, Nor Azman; Mohamed Amir, Nawaz Hussain; Mohamed Amin, Mohamed Azril; Goh, Kian Liang (2013)
Introduction: Pelvic tumour resections are complex and associated with extensive bleeding. Despite various blood management options in orthopaedic surgery, their used are limited particularly for pelvic tumour resections. Identifying predictive factors for a large amount of blood loss during surgery is essential.